2018
DOI: 10.1037/drm0000070
|View full text |Cite
|
Sign up to set email alerts
|

Dream content in pregnancy and postpartum: Refined exploration of continuity between waking and dreaming.

Abstract: The present study is an extension of previous work on the dreams of pregnant women, with a large sample from pregnancy and postpartum. In total, 143 pregnant women completed dream diaries during 3 distinct periods. Also, 125 nonpregnant women completed a dream diary on 1 occasion. Pregnancy-and motherhood-related oneiric characteristics, as well as negative versus positive dream elements, were coded by 2 independent judges. Results revealed that pregnant women experienced more direct in-dream representations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Finally, the control mastery theory suggests that dreams reflect concerns that could not be solved through conscious thoughts alone (Gazzillo et al, 2020). To illustrate the effect of concerns on dreaming, women in the process of divorce sometimes dream about their ex-spouse (Cartwright et al, 2006); individuals in bereavement tend to dream about their lost ones (Barrett, 1992;Black et al, 2019); pregnant women dream of pregnancy, childbirth, and motherhood more often than nonpregnant controls (Dagan et al, 2001;Lara-Carrasco et al, 2013;Nielsen & Paquette, 2007;Sabourin et al, 2018); individuals with a substance use disorder commonly experience drug dreams after withdrawal (Colace, 2014;Johnson, 2012); and a large proportion of students who anticipate an important exam dream about it (Arnulf et al, 2014). This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Adaptiveness Of Avoidance and Approach Behaviorsmentioning
confidence: 99%
“…Finally, the control mastery theory suggests that dreams reflect concerns that could not be solved through conscious thoughts alone (Gazzillo et al, 2020). To illustrate the effect of concerns on dreaming, women in the process of divorce sometimes dream about their ex-spouse (Cartwright et al, 2006); individuals in bereavement tend to dream about their lost ones (Barrett, 1992;Black et al, 2019); pregnant women dream of pregnancy, childbirth, and motherhood more often than nonpregnant controls (Dagan et al, 2001;Lara-Carrasco et al, 2013;Nielsen & Paquette, 2007;Sabourin et al, 2018); individuals with a substance use disorder commonly experience drug dreams after withdrawal (Colace, 2014;Johnson, 2012); and a large proportion of students who anticipate an important exam dream about it (Arnulf et al, 2014). This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Adaptiveness Of Avoidance and Approach Behaviorsmentioning
confidence: 99%
“…More specifically, continuity between dream content and waking life was observed within complex individual characteristics, such as personality ( 3 , 4 ), physical health ( 5 ), social roles ( 6 ) and individual concerns ( 7 , 8 ). It was also found that changes in psychological well-being are correlated with similar changes in emotional dream content ( 9 ) and significant life experiences such as pregnancy can be well represented with distortions in dreams ( 10 ). Schredl ( 11 ) has proposed a mathematical model of families of influencing factors and their interactions that mediate incorporation into dreams.…”
Section: Introductionmentioning
confidence: 97%
“…Various forms of health and illness have also been shown to impact dreams. Events such as pregnancy and surgeries are associated with dream imagery that is distinct from the imagery of individuals who were not experiencing the same health related events (Giordano et al, 2012; Sabourin, Robidoux, Pérusse, & De Koninck, 2018). Poorer physical health or physical functioning has been associated with more dreams involving bodily misfortunes, injuries, illness, and medical imagery.…”
mentioning
confidence: 99%